2007
DOI: 10.1111/j.1365-2885.2007.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline and its metabolites produce a stimulating cholinergic effect on the small intestine and a nonadrenergic noncholinergic relaxing effect on the colon: a comparative study in the rabbit intestine

Abstract: The present study examines comparatively the effects of theophylline and its metabolites, 1-methylxanthine (1-MX), 3-methylxanthine (3-MX), 1,3-dimethyluric acid (1,3-DMU) and 1-methyluric acid (1-MU) along the rabbit intestine, and explores the underlying mechanism(s). In the small intestine, theophylline produces atropine- and hexamethonium-sensitive increases in both the amplitude of phasic contractions and the basal tone. All metabolites mimic the theophylline's stimulating effect. In particular, concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…For theophylline, the most frequently DDI-related proteins are CYP1A2, CYP3A, cholinergic receptors, and adrenergic receptors. Experiments showed that theophylline (or its metabolites) could stimulate cholinergic effect [28]. Beta-adrenergic blockers may also interfere the effects of theophylline if they are taken together [29].…”
Section: Resultsmentioning
confidence: 99%
“…For theophylline, the most frequently DDI-related proteins are CYP1A2, CYP3A, cholinergic receptors, and adrenergic receptors. Experiments showed that theophylline (or its metabolites) could stimulate cholinergic effect [28]. Beta-adrenergic blockers may also interfere the effects of theophylline if they are taken together [29].…”
Section: Resultsmentioning
confidence: 99%
“…Theophylline and other PDE inhibitors not only decrease airway inflammation but also improve pulmonary function [15] by acting directly on bronchial tone to induce bronchodilation. In clinical use, theophylline has also been found to be effective on visceral smooth muscle spasm-induced symptoms [16-18]. However, neither the potency, nor the efficacy of drotaverine has been tested in respect of airway smooth muscle relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacology and rabbit [21,22], but also the guinea pig antrum [23], the rabbit fundus, antrum and pylorus [21], the rabbit distal [24] and ascending [25] colon, as well as the colon [26] and taenia coli [27] in the guinea pig. Conversely, a contractile effect of theophylline was also described on the stimulated guinea pig ileum [28][29][30], and more recently in the rabbit small intestine [25].…”
Section: Fundamental and Clinicalmentioning
confidence: 99%
“…Besides the relaxing effect of theophylline on the respiratory tissues in several animal species [9–14], man included [15–17], which underlies the clinical bronchodilator properties of the drug, a relaxing effect has been also demonstrated on gastrointestinal smooth muscle tissues. In particular, in vitro and in vivo studies have shown that theophylline relaxes the lower oesophageal sphincter (LOS) in man [18], opossum [19,20] and rabbit [21,22], but also the guinea pig antrum [23], the rabbit fundus, antrum and pylorus [21], the rabbit distal [24] and ascending [25] colon, as well as the colon [26] and taenia coli [27] in the guinea pig. Conversely, a contractile effect of theophylline was also described on the stimulated guinea pig ileum [28–30], and more recently in the rabbit small intestine [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation